Penerapan Algoritma K-Means Dalam Mengelompokkan Jumlah Penerimaan Sinyal Telepon Seluler Di Sumatera Utara - Sitompul, Wati Rizky Pebrianti; Solikhun, Solikhun; Saputra, Widodo; Oktaviani, Selli; windarto, agus perdana (Bulletin of Artificial Intelligence, 2023)
The purpose of this study was to cluster the number of cell phone signal reception in North Sumatra. The source of the data used is obtained from BPS. The variable used is the number of cell phone reception signals in North Sumatra. This research uses Data Mining Technique with K-means algorithm. It is hoped that the results of this study can provide input to the North Sumatra Province in order to determine the reception of cellular telephone signals, so as to increase the growth and development of telephone signal reception in North Sumatra. And 4G/LTE data obtained that there are 4 high clusters, namely (Mandailing Natal, Simalungun, Deli Serdang, Padang Lawas), 17 medium clusters, namely (Nias, South Tapanuli, Labuan Batu, Humbang Hasundutan, West Pakpak, Samosir, Labuhan Batu, South , Labuhan Batu Utara, North Nias, West Nias, Sibolga, Tanjung Balai, Pematangsiantar, Tebing Tinggi, Binjai, Padang Sidempuan, Gunung Sitoli), and there are 2 low clusters (Central Tapanuli, North Tapanuli, Toba, Asahan, Dairi, Karo , Langkat, South Nias, Serdang Bedagai, Batu Bara, North Padang Lawas, Medan).